Odpowiedzi

2010-01-18T17:48:56+01:00
A)11+(-12)+39+9-8=23-39+9-8=16+9-8=20-8=12 sory ino to znałam
1 1 1
2010-01-18T17:54:42+01:00
11+(-12)+39+9-8=39
45+(-9)+(-91)+5=-46
-4 1/2+1/6+(-1/2)+1 1/3=-3 3/6
6,25+(-1/4)+(-3/5)+0,75= 6,25
4/7+(-3/14)+1/14=6/14
1/2+(-3/4)+(-5/8)=-7/8
5 2/3+(-3 4/5)+1/3+(-1/5)=1 13/15
16 4/5+(-4,8)+3 1/5+(-4 1/5)=11
1 2 1
Najlepsza Odpowiedź!
2010-01-18T17:58:44+01:00
A)=11-12+39+9-8=39
b)=45-9-91+5=-50
c)=-4½+⅙-½+1⅓=-4 3/6 + 1/6 - 3/6 + 1 2/6 = -3 3/6 = -3 ½
d)=6,25-0,25-0,6+0,75=6,15
e)=4/7 - 3/14 + 1/14 = 8/14 - 3/14 + 1/14 = 6/14 = 3/7
f)=4/8 - 6/8 - 5/8 = -7/8
g)=5 10/15 - 3 12/15 + 5/15 - 3/15 = 2 6/15 = 2 2/5 = 2,4
h)=16,8-4,8+3,2-4,2= 11
2 3 2